The role of leaf height in plant competition for sunlight: analysis of a canopy partitioning model - Andrew L. Nevai; Richard R. Vance (Mathematical Biosciences and Engineering)
A global method of nullcline endpoint analysis is employed to de-termine the outcome of competition for sunlight between two hypotheticalplant species with clonal growth form that differ solely in the height at whichthey place their leaves above the ground. This difference in vertical leaf placement, or canopy partitioning, produces species differences in sunlight energycapture and stem metabolic maintenance costs. The competitive interactionbetween these two species is analyzed by considering a special case of a canopypartitioning model (RR Vance and AL Nevai, J. Theor. Biol. 2007, 245:210-219;AL Nevai and RR Vance, J. Math. Biol. 2007, 55:105-145). Nullcline endpointanalysis is used to partition parameter space into regions within which eithercompetitive exclusion or competitive coexistence occurs. The principal conclu-sion is that two clonal plant species which compete for sunlight and place theirleaves at different heights above the ground but differ in no other way can, un-der suitable parameter values, experience stable coexistence even though theyoccupy an environment which varies neither over horizontal space nor throughtime.